Detection and 2D Imaging of Dopamine Distribution Using a Closed Bipolar Electrode System by Applying a Cathodic Luminophore. Issue 18 (30th July 2021) - Iwama, Tomoki; Komatsu, Mayo; Inoue, Kumi Y.; Shiku, Hitoshi
Abstract: A 2D imaging system using closed bipolar electrodes (cBPEs) and electrochemiluminescence (ECL) is expected to realize high spatio‐temporal resolution imaging. However, imaging of the distributions of molecules that cause an oxidation reaction on the electrode surface was not achieved by the cBPE/ECL system because the conventionally used luminophore can generate ECL only by an oxidation reaction. In this paper, we propose to implement a cathodic luminophore, [Ru(bpy)3 ]Cl2 /glutathione disulfide (GSSG) producing ECL by reduction reaction into the cBPE/ECL system to enable detection and 2D imaging of dopamine, which is an oxidizable redox species and an important neurotransmitter. The applicability of [Ru(bpy)3 ]Cl2 /GSSG for dopamine detection using a single cBPE was shown and its electrochemical properties were discussed. In addition, the demonstration of the 2D imaging of dopamine was performed using a cBPE array. These results show the potential to greatly expand the applicability of detection and imaging systems using cBPE/ECL. Abstract : Cathodic electrochemiluminescence is applied on closed bipolar electrode (cBPE) systems using [Ru(bpy)3 ] 2+ /glutathione disulfide as a luminophore. Quantification and 2D imaging of the distribution of dopamine are demonstrated using a single cBPE and a cBPE array with the cathodic luminophore. These results show the possibility of expanding the analysis target of cBPE systems including bipolar electrochemical microscopy.